Analysis of real-time blockchain considering service level agreement (SLA) - Kim, Minkyung; Kim, Kangseok; Kim, Jai Hoon (Advances in Science, Technology and Engineering Systems, 2021)
The Blockchain technologies enable decentralized networking consisting of large number of nodes. To determine the shared states and failures of all nodes in a fully distributed peer-to-peer system, the appropriate consensus algorithm needs to be selected for each Internet of Things system. In this paper, a novel hierarchical voting-based byzantine fault tolerance (HBFT) consensus algorithm is proposed. The proposed HBFT algorithm utilizes a typical PBFT algorithm hierarchically to guarantee low latency. The message complexity of HBFT shows that our proposed algorithm has better scalability. We also mathematically calculate the optimal number of groups based on the total number of nodes to determine the ratio of allowable faulty nodes per group. In addition, we analyze the reliability of byzantine fault tolerance to compare the reliability of group case with the reliability of non-group case. Finally, we introduce the methods of real-time Blockchain considering the service level agreement (SLA). The real-time processing performance of transactions is analyzed for the service level agreement (SLA).
Keywords: Blockchain; Byzantine Fault Tolerance; Consensus Algorithm; Decentralized Framework; Internet of Things